Sport marketing and the internet - Sun, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The Internet is the frontier for sport marketers to build stronger relationships with consumers. The `virtual` communities of the Internet are a natural extension of the `communities` that form around sport organizations and teams. Firms are building brand equity and increasing brand loyalty through this new medium. There are, however, a myriad of challenges confronting marketers who test these new and largely unfamiliar water. This study was divided into three parts. Part profiled Internet users and explored how sports marketers utilize the Internet. Part 2 provided the results of an empirical study evaluating the features of major professional sports team websites (take the USA`s websites for example). The final section, reviewed the challenges and opportunities inherent in conducing market research on the Internet.